Association of gene TP53 polymorphic marker Pro72Arg with clinical characteristics of chronic glomerulonephritis - Elena Sergeevna Kamyshova; Mikhail Yur'evich Shvetsov; Aleksey Evgen'evich Shestakov; Irina Mikhaylovna Kutyrina; Valeriy Vyacheslavovich Nosikov; E S Kamyshova; M Yu Shvetsov; A E Shestakov; I M Kutyrina; V V Nosikov (Терапевтический архив, 2011)
Aim. To study association of geneTP53 polymorphic marker Pro72Arg coding synthesis of p53 protein with onset, course and progress of chronic glomerulonephritis (CGN). Material and methods. We examined 126 patients (63 males and 63 females, mean age 38.8±13.2 years) with CGN duration 13.0±9.1 years. When analyzing genetic predisposition to CGN, we compared incidence rate of alleles/genotypes of polymorphic marker Pro72Arg of gene TP53 in CGN patients and 69 controls free of renal disease. CGN clinical features were assessed retrospectively including analysis of nephritis onset, clinical and morphological variants. The course of CGN was analysed by changes in severity of hypertension, persistence of proteinuria > 3 g/day during 6 months and longer, conduction of immunosuppressive therapy and response to it. In analysis of progression rate, doubling of blood creatinine was considered as an end point. We used polymerase chain reaction with analysis of restriction fragment length for identification of alleles of Pro72Arg polymorphic marker of TP53 gene. Results. Distribution of the genotypes of the above polymorphic marker in CGN patients and in controls did not significantly differ. Depending on Pro allele carriage, CGN patients were divided into two groups: Arg/Arg group (59 carriers of genotype Arg/Arg) and Pro group (63 patients with genotype Arg/ Pro and 4 with genotype Pro/Pro). Carriage of Pro allele of gene TP53 was associated with high CGN activity at onset, presence of arteriolosclerosis and IgA deposits in kidney biopsy. Patients with genotype Arg/Arg more frequently developed nephritic syndrome without renal dysfunction syndrome. Conclusion. We have discovered association of geneTP53 polymorphic marker Pro72Arg with clinical manifestations of CGN. Carriers of Pro allele more often have signs of active glomerular inflammation and vascular impairment with renal dysfunction while carriers of Arg/Arg genotype more frequently demonstrate isolated nephritic syndrome.